Distinct psychological profiles and responsiveness to a brief intervention in workers with high versus low intensity emotional labor: an observational study - Dasom Lee; Nahyun Ha; Changyoung Oh; Ul Soon Lee; YoonJi Irene Lee; Do-Hyung Kang; Soo-Hee Choi (PLoS ONE, 2026)
Emotional labor refers to the process by which employees regulate and manage their emotions as part of their job requirements. This observational study examined distinct psychological profiles and differential responsiveness to a brief 35-minute mind-body training (MBT) among 753 emotional labor workers with high versus low emotional labor intensity. Participants were categorized into high-risk and low-risk groups based on their emotional labor intensity. Psychological measures included positive and negative affect (Positive and Negative Affect Schedule), depressed mood (Center for Epidemiologic Studies Depression Scale), and quality of life (World Health Organization Quality of Life-Brief Version). Resting heart rate was obtained from a limited sample ( n = 29) for exploratory analysis. At baseline, among emotional labor subscales, emotional disharmony and hurt was associated with increased depressed mood and decreased quality of life in both groups ( p < .001), while lack of a supportive and protective system in the organization positively correlated with depressed mood in the high-risk group only ( p = .040). After the MBT, the high-risk group showed greater decrease in negative affect compared to the low-risk group ( p < .001). Exploratory analysis showed heart rate decreased significantly regardless of group ( p = .039), with greater reductions in employees reporting higher baseline emotional demand and regulation ( r = .464, p = .01). Our results suggest that high-risk workers, particularly those lacking organizational support, may exhibit greater psychological vulnerabilities but also greater responsiveness to workplace intervention, providing preliminary evidence for considering emotional labor intensity when designing workplace interventions.